EFFECT OF IMPLEMENTATION OF FINTECH STRATEGIES ON COMPETITIVENESS IN THE BANKING SECTOR IN KENYA: A CASE OF KCB BANK KENYA - Kemunto, Eunice Rabera; Kagiri, Dr. Assumpta (European Journal of Business and Strategic Management, 2018)
Purpose: The purpose of this study was to establish the effects of implementation of Fintech strategies on competitiveness in the banking sector in Kenya Methodology: The study was based on the descriptive research design. The target population of this study is Kenya Commercial Bank branches in Nairobi Central Business District (CBD). There are 12 KCB branches in Nairobi CBD. The sampling frame for this study consist of managerial level employees from Operations, Corporate & Regulatory Affairs, Credit, Risk, Human Resources, Information Technology and, Finance departments from these branches. Herein, either a senior or an assistant manager from each of these 7 departments of the 12 bank branches was targeted. This made a total of 84 employees. The study utilized primary data collected using a structured questionnaire. Data was analyzed using descriptive and inferential methods. This was done using SPSS statistical package. The findings obtained were presented in Tables. Results: The study found that an increase in e-banking; mobile banking; agency banking and; process automation would lead to increase in competitiveness in commercial banks respectively. This shows that the strongest factor influencing competitiveness in commercial banks was mobile banking followed by process automation. The third most important independent variable was agency banking. Conversely, the least influencer of the competitiveness in commercial banks was internet banking. Policy recommendation: the study recommends that banks should strengthen its fintech strategies so as to enhance their competitiveness. Lastly, the study recommends follow-up studies that extensively investigate each of the study variables as well as other fintech strategies that affect the competitiveness of commercial banks need to be studied. The moderate influence of other strategies that banks implemented on this study could also avail valuable information.